2016
DOI: 10.1016/s2352-3018(16)30039-x
|View full text |Cite
|
Sign up to set email alerts
|

Providing a conceptual framework for HIV prevention cascades and assessing feasibility of empirical measurement with data from east Zimbabwe: a case study

Abstract: SummaryBackgroundThe HIV treatment cascade illustrates the steps required for successful treatment and is a powerful advocacy and monitoring tool. Similar cascades for people susceptible to infection could improve HIV prevention programming. We aim to show the feasibility of using cascade models to monitor prevention programmes.MethodsConceptual prevention cascades are described taking intervention-centric and client-centric perspectives to look at supply, demand, and efficacy of interventions. Data from two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 19 publications
(23 reference statements)
0
73
0
Order By: Relevance
“…We used this approach to highlight low service utilization for each intervention type [16], acknowledging the following: 1) the heterogeneity of prevention needs represented among diverse groups of men who have sex with men; and 2) the complex web of interacting HIV prevention modalities [17]. The number of participants who tested for HIV and received results served as the denominator for determining steps along the cascade.…”
Section: Methodsmentioning
confidence: 99%
“…We used this approach to highlight low service utilization for each intervention type [16], acknowledging the following: 1) the heterogeneity of prevention needs represented among diverse groups of men who have sex with men; and 2) the complex web of interacting HIV prevention modalities [17]. The number of participants who tested for HIV and received results served as the denominator for determining steps along the cascade.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier analyses of Manicaland Cohort data on risk among AGYW indicated unprotected sexual relationships with older men contribute to their high HIV incidence . Preliminary analyses of the HIV prevention cascade for other prevention methods among AGYW found gaps in perceptions about personal HIV infection risks . Lack of risk perception indicates lack of motivation to use HIV prevention methods.…”
Section: Discussionmentioning
confidence: 99%
“…VMMC is central in Zimbabwe's HIV prevention programme, but only 10% of men (15- circumcised in Manicaland [23] and uptake is off-track to meet national targets [28]. Previous HIV prevention cascade analysis using Manicaland Cohort data found that low VMMC uptake in the study population was largely due to low risk perception for HIV infection, suggesting gaps in motivation and poor local availability [2]. Motivation for VMMC uptake can be affected by negative perceptions of its consequences.…”
Section: Selection Of Interventionsmentioning
confidence: 99%
“…1), besides critical enablers and synergies with other development sectors. Inspired by the 90-90-90 target for testing and treatment [19][20][21], recent work has proposed CASCADE analyses for monitoring and managing primary prevention programmes [22]. In addition, future monitoring will need to harness the power of new technologies, allowing the electronic collection of data from all health facilities and all community-based service delivery platforms as well as from commodity distribution systems (e.g.…”
Section: Synergies With Development Sectorsmentioning
confidence: 99%